Pengkategorian Item Penulisan Dalam Karya Fiqh Melayu Klasik: Analisa Awal: Recruiting Items in Classic Field Fiqh Work: An Effective Analysis - Abdul Malik, Mohd Puaad; Abdul Hamid, Ahmad Faisal (Journal Al-Muqaddimah, 2020)
The writing of classical Malay fiqh is a manifestation of the ability and intellectual ability of Malay scholars to write and produce high-quality science. Undoubtedly, it contributes to intellectual value creation among Malay scholars who seek to make the best contribution to society. The premise of this article discusses the categorization of writing items resulting from the writing and creation of classical Malay fiqh. It covers subject-writing items and chronological discussions, physical work, author status as an initial discussion on the category of items of Malay fiqh works. The categorization of these writing items is thought to have had an impact on the development of Malay fiqh works in the Malay Nature region as it came from high impact writing and beneficial to the Muslim Malay community. The intellectual and intellectual writing elements of the past were used as guides and references to our lives today. In addition, the development of Malay fiqh works is dynamic, non-static. It flourishes by the flow of times and there is a growing fiqh knowledge in the writing of Malay fiqh by centuries and times.